Anger, Madness, And The Daimonic: Toward An Existential Depth Psychology (Existential Analysis: Journal of the Society for Existential Analysis, 1999)
"Existential Therapy" is gaining popularity among sophisticated clinicians seeking more pragmatic yet philosophically and spiritually grounded approaches to psychotherapy. Yet the term "existential psychotherapy" has come to connote a confusing array of varied and wildly divergent treatments - from more traditional analytic methods of "body-work" to Viktor Frankl's "logotherapy" to "philosophical counseling" or "clinical philosophy" to Zen meditation. What is existential psychotherapy? How does it differ from existential philosophy? Dr. Diamond observes that existential psychotherapy has developed somewhat differently in Europe than in America, emphasizing that existential therapy emerged at least as much from the depth psychology of Freud, Adler, Rank and Jung as from the philosophical musings of Sartre, Nietzsche, Heidegger and Kierkegaard - thus making it most truly an existential depth psychology. However, rather than dwelling on differences, he proposes reconciliation - not only between continental divides, but between the realms of existential therapy and depth psychology. While some find the principles of existential therapy antithetical and incompatible with those of depth psychology - particularly regarding the notion of the "unconscious" - Diamond dismisses such objections as primarily reactive partisan and parochial dogma, stressing instead the eminent compatibility, complementarity, and practical clinical utility of these two valid world views when conjoined. He defines existential depth psychology as a holistic approach grounded in Rollo May's paradoxical paradigm of the daimonic. One of the foremost tasks of such an approach must be to phenomenologically explore the growing epidemic of pathological anger, rage and violence, and the problem of human evil in general.